Enhancing Workplace Well-Being: Employee Perspective - Karaca, Gizem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The primary purpose of the research is to analyze the factors associated with the nurses’ Eudaimonic Workplace Well-being. Firstly, the study examines the influence of shared values on eudaimonic workplace well-being, and the potential for perceived organizational justice and emotional exhaustion to act as mediators in this relationship. Also, the research analyses the effect of perceived organizational support on eudaimonic workplace well-being, while exploring how emotional exhaustion and job satisfaction serve as mediators in this relationship. Using data collected from three hundred nurses in Turkish healthcare institutions during the COVID-19 pandemic (Male=113, Female=187). The age of participants ranged from 19 to 58 and the average age was 34. The snowball sampling method was used to form our sample and self-administered surveys that could be completed online were delivered to the sampled nurses. Our analysis using Partial Least Square Structural Equation Modelling (PLS-SEM) supported the expected relationship between shared values and eudaimonic workplace well-being as well as the mediating role of perceived overall justice and emotional exhaustion. We also show a serial mediation where perceived organizational support is related to emotional exhaustion which in turn negatively related to job satisfaction which subsequently related to higher levels of eudaimonic workplace well-being. The present study contributes to nursing and management literature by examining antecedents of eudaimonic well-being. Furthermore, our findings provide implications for the mental health of frontline employees in health organizations to have higher levels of eudaimonic well-being which is especially important in times of intense pressure such as the period during the COVID-19 pandemic.

ÖZ: Araştırmanın birincil amacı, hemşirelerin Eudaimonik İşyeri İyi Oluşu ile ilişkili faktörleri analiz etmektir. İlk olarak çalışma, paylaşılan değerlerin eudaimonik işyeri refahı üzerindeki etkisini ve algılanan örgütsel adalet ile duygusal tükenmenin bu ilişkide arabulucu olarak hareket etme potansiyelini incelemektedir. Ayrıca araştırma, algılanan örgütsel desteğin eudaimonik işyeri refahı üzerindeki etkisini analiz ederken, duygusal tükenme ve iş tatmininin bu ilişkide nasıl aracılık ettiğini araştırıyor. Çalışmada kullanılan veriler, COVID-19 salgını sırasında, Türk sağlık kurumlarında çalışan üç yüz hemşireden toplanmıştır (Erkek=113, Kadın=187). Katılımcıların yaşları 19 ile 58 arasında değişmekte olup, yaş ortalaması 34'tür. Örneklemimizi oluşturmak için snowballing (kartopu) örnekleme yöntemi kullanılmış ve örneklemi oluşturan hemşirelere online olarak doldurulabilen kendi kendine uygulanan anketler ulaştırılmıştır. Kısmi En Küçük Kareler Yapısal Eşitlik Modellemesini (PLS-SEM) kullanarak yaptığımız analiz, paylaşılan değerler ile eudaimonik işyeri refahı arasındaki beklenen ilişkiyi ve algılanan genel adalet ve duygusal tükenmenin aracı rolünü destekledi. Ayrıca, algılanan örgütsel desteğin duygusal tükenme ile ilişkili olduğu ve bunun da iş tatmini ile negatif olarak ilişkili olduğu ve daha sonra daha yüksek eudaimonik işyeri refahı ile ilişkili olduğu bir dizi arabuluculuk gösteriyoruz. Bu çalışma, eudaimonik iyi oluşun öncüllerini inceleyerek hemşirelik ve yönetim literatürüne katkıda bulunmaktadır. Ayrıca, bulgularımız, sağlık kuruluşlarındaki ön saflarda çalışanların ruh sağlığının, özellikle COVID-19 salgını dönemi gibi yoğun baskı zamanlarında önemli olan daha yüksek düzeyde eudaimonik iyi oluşa sahip olması için çıkarımlar sağlıyor.
Doctor of Philosophy in Business Administration. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2023. Supervisor: Prof. Dr. Cem Tanova
Keywords: Business Administration Department; Workplace--Employee health promotion; Workplace communication; Employee health promotion--Job satisfaction--Management; Job Stress--Employees--Mental health; Work--Physiological aspects; Shared values, emotional exhaustion, perceived overall justice, perceived organizational support, job satisfaction, eudaimonic workplace well-being